Researching language and social media : a student guide - Page, Ruth E., 1972-; Barton, David, 1949-; Lee, Carmen; Unger, Johann Wolfgang; Zappavigna, Michele (New York, Routledge, 2022)
"Researching Language and Social Media: A Student Guide introduces the linguistic frameworks currently used to analyse language found in social media contexts. This highly accessible guidebook outlines the practical steps and ethical guidelines entailed when gathering linguistic data from social media sites and platforms. In this new edition, the authors update the range of social media interactions used as examples and draw attention to important developments such as 'fake news' and new areas of debate such as hate speech. Expanding the geographical and multilingual aspects, this edition also includes examples from Asia and the Arabic-speaking world. With updated methods that help students study the language of social media from a multimodal perspective, the recent up-take in image sharing, video-chat and graphicons will also be addressed. Each chapter begins with a clear summary of the topics covered and also suggests sources for further reading to supplement the initial discussion and case studies. This timely book is an essential guide for students of English language and linguistics, media and communication studies"--
Includes bibliographical references and index.
Keywords: Communication -- Technological innovations; Language and languages -- Usage; Human-computer interaction; Technological innovations -- Social aspects; Social media